2023
DOI: 10.1007/s12325-022-02392-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of SAPIEN 3 Transcatheter Aortic Valve Implantation Versus Surgical Aortic Valve Replacement in German Severe Aortic Stenosis Patients at Low Surgical Mortality Risk

Abstract: Introduction: In the randomized PARTNER 3 trial, transcatheter aortic valve implantation (TAVI) with the SAPIEN 3 device significantly reduced a composite of all-cause death, stroke, and rehospitalization, compared with surgical aortic valve replacement (SAVR), in patients with severe symptomatic aortic stenosis and low risk of surgical mortality. Furthermore, TAVI has been shown to be cost-effective in low-risk patients, compared with SAVR, in a number of countries. This study aimed to determine the cost-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The results found that TAVI dominated SAVR in terms of an increase in QALYs of 0.94 and cost saving of e3013 per patient, thus providing meaningful clinical and cost benefits over SAVR. The result is aligned with a range of published CEAs for other European countries, with the exception of England (Figure 2) [10][11][12][13][14][15][16].…”
Section: What Is Cost-effectiveness Analysis?supporting
confidence: 76%
“…The results found that TAVI dominated SAVR in terms of an increase in QALYs of 0.94 and cost saving of e3013 per patient, thus providing meaningful clinical and cost benefits over SAVR. The result is aligned with a range of published CEAs for other European countries, with the exception of England (Figure 2) [10][11][12][13][14][15][16].…”
Section: What Is Cost-effectiveness Analysis?supporting
confidence: 76%
“…The value of TAVI for intermediate‐ and high‐risk patients is relatively well proven (Table 2), 48,52–58 and the cost‐effectiveness of TAVI for low‐risk patients using contemporary devices, procedural planning, and optimized intraprocedural and postprocedure care may be expected to provide advantages in survival and QoL 17,59–61 . TAVI has been shown to offer meaningful benefits over SAVR in providing both savings in healthcare costs and in improvement in health‐related QoL for patients with SAS at low risk of surgical mortality in multiple healthcare systems across Europe, United States, and Canada 60,62–65 . Data from the United States suggest that continued efforts to expand the use of both the minimalist approach and a streamlined TAVI clinical pathway are likely to substantially improve the cost‐effectiveness of this procedure 18 …”
Section: Resultsmentioning
confidence: 99%
“…17,59-61 TAVI has been shown to offer meaningful benefits over SAVR in providing both savings in healthcare costs and in improvement in health-related QoL for patients with SAS at low risk of surgical mortality in multiple healthcare systems across Europe, United States, and Canada. 60,[62][63][64][65] Data from the United States suggest that continued efforts to expand the use of both the minimalist approach and a streamlined TAVI T A B L E 2 Cost-effectiveness of TAVI across the spectrum of surgical risk. | 553 clinical pathway are likely to substantially improve the costeffectiveness of this procedure.…”
Section: Cost-effectiveness Of Tavimentioning
confidence: 99%
“…Nos últimos anos, várias abordagens contemporâneas têm sido desenvolvidas para tratar a estenose aórtica, incluindo a substituição valvar aórtica transcateter (TAVR) e a cirurgia valvar aórtica minimamente invasiva (MIAVR). Essas novas abordagens apresentam muitas vantagens em relação às técnicas convencionais, como a cirurgia de válvula aórtica aberta, incluindo menor tempo de recuperação, menor tempo de internação hospitalar e menor trauma cirúrgico (CHEN CG, et al, 2022;KUCK KH, et al, 2023) A TAVR é uma técnica minimamente invasiva que envolve a colocação de uma nova válvula aórtica através de um cateter inserido na artéria femoral. A técnica é indicada para pacientes com alto risco cirúrgico ou que não são candidatos à cirurgia valvar aórtica aberta convencional.…”
Section: Discussionunclassified
“…A técnica é indicada para pacientes com alto risco cirúrgico ou que não são candidatos à cirurgia valvar aórtica aberta convencional. A cirurgia valvar aórtica minimamente invasiva, por sua vez, é realizada através de pequenas incisões na parede torácica e oferece uma recuperação mais rápida e menos dolorida para o paciente em comparação com a cirurgia valvar aórtica aberta convencional (KUCK KH, et al, 2023).…”
Section: Discussionunclassified